2023
DOI: 10.1177/17474930231154797
|View full text |Cite
|
Sign up to set email alerts
|

Good collaterals and better outcomes after EVT for basilar artery occlusion: A systematic review and meta-analysis

Abstract: Background: Stroke caused by acute basilar artery occlusion (BAO) is devastating with high dependency and mortality. Recent trials have demonstrated the efficacy of endovascular treatment (EVT) for acute BAO, while pretreatment collaterals may be a valuable prognostic indicator for post-EVT outcomes. Aims: To systematically review and synthesize evidence on the associations between pretreatment collateral status and outcomes after EVT in acute BAO. Methods: We retrieved relevant full-text articles published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…A recent meta-analysis encompassing 16 real-world cohort studies demonstrated that the presence of robust pretreatment collaterals in BAO patients undergoing EVT was associated with a two-fold likelihood of favorable outcomes at 90 days, a higher probability of successful recanalization, and reduced odds of mortality compared to those with poor collaterals. 33 In our study, we further revealed that a low BATMAN score, which assesses thrombus burden and collateral status, could independently predict FR after EVT in BAO patients, with an AUC of 0.724 (95% CI: 0.589–0.859) and an optimal cut-off value of 7. However, a previous study proposed a BATMAN score of 3 as the optimal threshold for predicting FR following EVT in BAO stroke.…”
Section: Discussionsupporting
confidence: 61%
“…A recent meta-analysis encompassing 16 real-world cohort studies demonstrated that the presence of robust pretreatment collaterals in BAO patients undergoing EVT was associated with a two-fold likelihood of favorable outcomes at 90 days, a higher probability of successful recanalization, and reduced odds of mortality compared to those with poor collaterals. 33 In our study, we further revealed that a low BATMAN score, which assesses thrombus burden and collateral status, could independently predict FR after EVT in BAO patients, with an AUC of 0.724 (95% CI: 0.589–0.859) and an optimal cut-off value of 7. However, a previous study proposed a BATMAN score of 3 as the optimal threshold for predicting FR following EVT in BAO stroke.…”
Section: Discussionsupporting
confidence: 61%
“…This is supported by a comprehensive meta-analysis performed by Liu et al., which is also in this month’s issue. 25 Good pre-treatment collaterals were associated with a doubled rate of favorable/good 90 day functional outcome (Relative Risk (RR) = 2.03, 95% confidence interval [CI]: 1.63–2.51, p < 0.001), a higher rate of successful recanalization (RR = 1.23, 95% CI: 1.04–1.45, p = 0.015), and reduced 90 day mortality (RR = 0.59, 95% CI: 0.43–0.81, p = 0.001) after endovascular treatment (EVT) for BAO.…”
mentioning
confidence: 99%